Pabrik Gula Kalibagor: Perkembangan dan Dampaknya Terhadap Kondisi Sosial Ekonomi Masyarakat Kalibagor Tahun 1957-1997 - Pamikat, Renardi; Wasino, Wasino; Atno, Atno (Journal of Indonesian History, 2019)
Sukarno's speech on August 17, 1956 signaled the takeover of Dutch-owned companies, which began in December 1957. The Law set up for the nationalization act was Law No. 86 of 1958. One of the things nationalized by the government was the Kalibagor sugar factory. In this study, the author discusses how the process of nationalizing the Kalibagor sugar factory until its closure and the socio-economic dynamics of the community that occurred after nationalization. The results of this study are that the people in Kalibagor experienced some changes. This is the impact of the nationalization. In 1975, the sugar commodity was replaced by rice and tobacco. Then the government issued Presidential Instruction No. 9 of 1975 concerning People's Intensification Sugar Cane (TRI). But the program was also unsuccessful with a number of problems, which made the Kalibagor sugar factory continue to suffer losses. Finally, in 1997 the crisis that occurred in Indonesia resulted in a decline in the sugar industry, so that there were several sugar mills which were closed or diamalgamasi including the Kalibagor sugar factory. Keywords: Kalibagor Sugar Factory, Nationalization, Impact